2020
DOI: 10.1111/jerd.12622
|View full text |Cite
|
Sign up to set email alerts
|

Clinical evaluation of a universal adhesive in non‐carious cervical lesions

Abstract: Objectives: To compare the clinical performance of a universal adhesive in class V non-carious cervical lesions (NCCLs) using two surface treatment protocols (self-etch [SfE] vs selective-enamel-etch [SelE]). Material and methods: Thirty-three adults, each with ≥2 NCCLs, received one resin composite restoration utilizing a SfE universal adhesive and another utilizing the adhesive and SelE with 37% phosphoric acid. Restorations were evaluated for sensitivity, retention, marginal discoloration, marginal adaptati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 20 publications
1
5
0
Order By: Relevance
“…In the present study, the same results were observed, given that, five lost restorations were in premolar (two maxillary and three mandibular) and two in maxillary incisors in agreement with Heymann's results [35]. This seems to be the reason that explains why, in many studies in which clinical follow-up of adhesive restorations in NCCL was performed, both anterior and posterior teeth were included [36][37][38][39][40][41].…”
Section: Recurrence Of Cariessupporting
confidence: 90%
“…In the present study, the same results were observed, given that, five lost restorations were in premolar (two maxillary and three mandibular) and two in maxillary incisors in agreement with Heymann's results [35]. This seems to be the reason that explains why, in many studies in which clinical follow-up of adhesive restorations in NCCL was performed, both anterior and posterior teeth were included [36][37][38][39][40][41].…”
Section: Recurrence Of Cariessupporting
confidence: 90%
“…43 Adhese Universal (ADU, Ivoclar Vivadent, Amherst, NY) resulted in very good in vitro and clinical results after up to 3 years. 55,[59][60][61] The E&R strategy showed less marginal discoloration and better marginal adaptation than the SE approach. In addition, the retention rate of ADU in NCCLs was not affected by dentin roughness created with a diamond but regardless of the adhesion strategy.…”
Section: Clinical Studies With Universal Adhesivesmentioning
confidence: 93%
“…The E&R and the selective enamel etching strategies provided better clinical outcomes with All‐Bond Universal (Bisco, Inc., Schaumburg, IL) and Gluma Universal (Kulzer North America, South Bend, IN) at 2 years 43 . Adhese Universal (ADU, Ivoclar Vivadent, Amherst, NY) resulted in very good in vitro and clinical results after up to 3 years 55,59‐61 . The E&R strategy showed less marginal discoloration and better marginal adaptation than the SE approach.…”
Section: Universal Adhesivesmentioning
confidence: 99%
“…We utilized a universal adhesive in self-etch mode with the aim of reducing the number of clinical steps involved in restoration, thereby decreasing the likelihood of clinical errors. Research has indicated that self-etch mode is superior to total etch [ 37 ] or comparable to selective etch in terms of clinical performance [ 38 ]; other findings have indicated no significant effect of bonding strategy [ 39 ]. Notably, however, conflicting results are present in the literature.…”
Section: Discussionmentioning
confidence: 99%